2014
DOI: 10.1016/j.bpj.2014.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene Photoisomerization-Induced Destabilization of B-DNA

Abstract: Molecular photoswitches provide a promising way for selective regulation of nanoscaled biological systems. It has been shown that conformational changes of azobenzene, one of the widely used photoswitches, can be used to reversibly control DNA duplex formation. Here, we investigate the conformational response of DNA upon azobenzene binding and isomerization, using a threoninol linker that has been experimentally investigated recently. To this end, nonequilibrium molecular dynamics simulations are carried out u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…It should also be noted that our previous results for an azobenzene in DNA with the LT linker and without any moiety in the opposite strand showed destabilization of DNA only at elevated temperature. 29 One of the main ingredients of our analysis has been the construction of a suitable local reference frame. The implementation of such a local frame not only is helpful for this particular analysis but also provides a general approach to deal with the structural changes of any nonresidual or foreign molecule covalently bound to the system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should also be noted that our previous results for an azobenzene in DNA with the LT linker and without any moiety in the opposite strand showed destabilization of DNA only at elevated temperature. 29 One of the main ingredients of our analysis has been the construction of a suitable local reference frame. The implementation of such a local frame not only is helpful for this particular analysis but also provides a general approach to deal with the structural changes of any nonresidual or foreign molecule covalently bound to the system.…”
Section: Resultsmentioning
confidence: 99%
“…41 The stacking interactions between any two bases can be mapped by monitoring either the center of mass distances or the buried surface area (BSA) between the bases and comparing them against mean values of these parameters obtained from reference simulations. 24,29 Here, we refer to the BSA, as in ref 29, but adopt a slightly modified approach to calculate the stacking stability. Let us consider the distribution of BSA between two bases calculated from a native RNA simulation where the bases remain visually stacked.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…86,87 Evidently, molecular dynamic simulations and T m experiments of duplexes have both indicated that the stabilizing effect is sufficient to offset the asymmetric distortion in DNA backbones resulted from the addition of azobenzene residues. 88,89 This makes it feasible to use azobenzene as a noninvasive molecular switch for controlling TMSD reactions in DNA seesaw circuits without sacricing sequence specicity.…”
Section: Leveraging Azobenzene-functionalized Oligonucleotides In Tmsmentioning
confidence: 99%